Adubação nitrogenada na cultura do milho com ureia revestida por diferentes fontes de polímeros - Valderrama, Marcio [UNESP]; Buzetti, Salatier [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Sabin Benett, Cleiton Gredson; Andreotti, Marcelo [UNESP] (Univ Estadual Londrina, 2014)
In view of theoretic increase in efficiency of nitrogen fertilizers for controlled release, this study aimed to evaluate the effect of nitrogen, using conventional urea and ureas coated by different polymers, in the leaf N content, leaf chlorophyll index, components production and grain yield of irrigated corn in growing season and second crop in the savannah region. The experiments were conducted at experimental area belonging to UNESP - Ilha Solteira, located in Selviria - MS in a dystrophic Red Latosol (Haplustox), clayey texture. The statistical design was randomized blocks, with four repetitions, in a 4 x 4 factorial arrangement, being four nitrogen doses (0, 40, 80 and 120 kg ha(-1)) applied at sidedressing and four urea sources (a conventional urea and three coated with polymers in different compositions and concentrations). The coated ureas are not efficient under the soil and climate conditions studied of the savanna, because they provided results similar to the conventional urea for the production components and grain yield of corn in the first and second crop. The increment of nitrogen doses increase linearly the leaf N content and grain yield of corn in the first and second crop.
Nitrogen fertilization in corn with urea coated with different sources of polymers
Keywords: Zea mays L.; nitrogen; coated fertilizer; no-tillage system; savannah soil